2020
DOI: 10.1021/acs.jpcc.0c03360
|View full text |Cite
|
Sign up to set email alerts
|

Controlling Aggregation and Excited-State Intramolecular Proton Transfer in BODIPYs by Incorporation of 2-(2-Hydroxyphenyl)quinazoline and Variation of Substituents

Abstract: A series of BODIPY-based AIEgens (QB1−QB5 and Bis-QB) containing 2-(2-hydroxyphenyl)quinazoline have been synthesized and thoroughly characterized. Photophysical properties of these compounds in solution and the aggregated state have been meticulously investigated and fine-tuned via structural modifications. These display green emission (∼530 nm) in solution and bright red emission (600−655 nm) in the aggregated/solid state with increased quantum yield. Crystal structure analyses and spectral studies revealed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 62 publications
0
20
0
Order By: Relevance
“…The emission intensity enhanced gradually with increasing DE fractions up to f DE 80%, and subsequently, it increased dramatically at f DE ≥ 80 (up to an f de of 99%) . Abrupt enhancement of the emission intensity at f DE 90 and 99% clearly suggested efficient aggregate formation .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The emission intensity enhanced gradually with increasing DE fractions up to f DE 80%, and subsequently, it increased dramatically at f DE ≥ 80 (up to an f de of 99%) . Abrupt enhancement of the emission intensity at f DE 90 and 99% clearly suggested efficient aggregate formation .…”
Section: Resultsmentioning
confidence: 99%
“…Notably, increasing the DE fraction up to f de 80% led to gradual aggregate formation and small emission enhancement. On the other hand, at high DE fractions ( f DE of 90 and 99%), efficient aggregate formation occurred with dramatic emission enhancement . Thus, it is concluded that this novel BODIPY clearly exhibits good emission enhancement due to aggregate formation and shows AIE features.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations